THE ROLE OF DIGITALIZATION IN THE PUBLIC PROCUREMENT SYSTEM - Баходир Исраилов (Bright Mind Publishing, 2026)
The article discusses the role of digitalization in the public procurement system as a key factor in improving the efficiency, transparency and competitiveness of procurement procedures. The main directions of digital transformation of public procurement in developed countries are analyzed, and the advantages of introducing electronic platforms and automated tools are determined. Conclusions are drawn about the importance of digitalization for reducing corruption risks and optimizing budget spending.
Keywords: Public procurement, digitalization, e-procurement, transparency, information technology.